Reading Burgesss A Clockwork Orange: Cultural Oddities and Their Social Impact - Ahmed, Mohammad Kaosar; Rahman, Md Mizanur (IIUC Studies, 2012)
Anthony Burgesss A Clockwork Orange (1962) portrays the disintegration of the traditional British culture and the rise of a new youth culture in revolt which produced violence and perversity. This youth culture started pervading the layers of the traditional British culture. The 1960s had found the British culture assuming a distorted shape both in values and norms - a culture completely opposite to its original tradition in terms of the socioeconomic changes that took place following the Second World War. The postwar generation had to peep into the collapsed world from a perspective quite different from the previous one because of the rising tension emerging out of a new threat from nuclear war hanging overhead. This paper seeks to explore the extent to which the newly emerged culture affected the young generation and brought about chaos and disorder in British society. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12260 IIUC Studies Vol.7 2011: 63-72